Modeling of Binary Logistic Regression in the Event of Childhood Diarrhea in Indonesia - Tofan Pramesi Wibowo; Soenarnatalina Melaniani; LutfiAgus Salim (Institute of Medico-legal Publications Pvt Ltd, 2021)
Logistic regression or logit regression is a statistical technique used to create predictive modeling. To determine the logistic regression equation that will be used to predict the value of the dependent variable, parameter estimates must be sought in the logistic regression model, one of the methods in this study uses the maximum likelihood method. The 2017 Indonesian Demographic and Health Survey (IDHS) collected various information, including about toddler diarrhea. Therefore, the logistic regression method is the right method to use in this condition, considering that the diarrhea data collected in the IDHS are categorical data. In this study, the variables influencing toddler diarrhea werechild age, birth size (average),exclusive breastfeeding, maternal age, maternal education (high school), wealth index (top), and latrine facilities The results of the logistic regression analysis showed that the variable with the highest risk figure for reducing the diarrhea rate was wealth index (top) (OR=1,438).